(untitled) (قضايا سياسية, 2022)
The study addresses the efforts by the Organizations of the Iraqi civil communities( OICC) in order to prevent the Iraqi Civil Status Law of 1959 AD from being subject to attempts to be changed or emptied it from its content.(OICC)worked in cooperation with many Iraqi bodies and figures to cancel the decision No. 137 which was issued in 2004 by the (Governing Council) which aims to cancel the Iraqi Civil Status Law and restoration of the doctrinal judiciary .(OICC) also worked to abolish AL- Jafari Status Bill which is presented in2014 as a substituent of Iraqi Civil Status Low .they have made good use of several means to achieve their objectives through multi-media symposiums ,uprising (vigils) , submitting protest notes to the government and parliament to have the assistance of some who work in the government and parliament and to have the support some clerics, and seeking the international Organization/ CEDAW Committee. Consequently, the article 41th of the constitution was cancelled and was considered as one of controversial articles, and AL- Jafari Status Bill was reserved . However attempts by some parliamentarians to change the Iraqi civil low are still ongoing .